(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article talks about handicraft products necessary for the daily life of residents of the Surkhan oasis in the beginning of the 19th-20th centuries, goods produced by the residents, types of handicrafts formed in the oasis from the early Iron Age to the present day